Research on a method for the evaluation of the pollution status of light petroleum hydrocarbon-contaminated sites via AHP-PSO - Bian, Han-liang; Lv, Bo-wen; Liu, Song-yu; Chu, Ya; Zhang, Jianwei (Stochastic environmental research and risk assessment, 2025)
The contamination state of soil can change significantly after contamination by light petroleum hydrocarbons. To assess these changes accurately, clay from Nanjing, Jiangsu Province, was selected as the research subject, and the basic parameters of the soil, soil state-related parameters, and contaminated site parameters were examined. A comprehensive evaluation method combining the analytic hierarchy process (AHP) and the particle swarm optimization (PSO) algorithm was established. In the method, the AHP was used to construct an evaluation system and optimize the weight values through PSO to reduce the errors caused by subjective assessments, ultimately calculating the pollution index (SQ) to assess the degree of contamination. For diesel-contaminated silty clay and kerosene-contaminated clay with varying oil contents (0%, 2%, 4%, 6%, 8%, and 10%), the results showed that the degree of impact of petroleum hydrocarbon contamination at a site is closely related to site type. A 2% oil content has a moderate impact on industrial sites and a severe impact on residential sites. As the oil content increases to 4%, 6%, 8% and 10%, the pollution status of both industrial and residential land reaches severe levels. The results of this study provide an important reference for determining the impact of light petroleum hydrocarbon pollution on soils and sites and for verifying the validity of the AHP-PSO method in the assessment of soil pollution status.